Electroencephalography in Orthostatic Tremor: A Prospective Study of 30 Patients. Issue 1 (21st May 2021) - Hellman, Amy; Bertoni, John M.; Bhatti, Danish E.; Murr, Najib; Torres-Russotto, Diego
Background: Orthostatic tremor (OT) is characterized by a sensation of instability while standing, associated with high frequency (13–18 Hz) tremor in the legs. Small retrospective series have reported electroencephalography (EEG) findings in OT with discordant results. Methods: We prospectively enrolled 30 OT subjects. Mean age = 68.3 (range 54–87) with mean disease duration 16.3 years (range 4–44). A modified 10–20 system EEG recording with additional midline electrodes was obtained. EMG electrodes were placed on quadricep muscles. EEG recording was performed at rest, during sleep and while standing unassisted. Results: In all subjects, EEG showed normal background, normal drowsiness and/or stage 2 sleep, and normal responses to hyperventilation and photic stimulation. These normal results persisted during stance. EEG abnormalities were found in 3 subjects (anterior-mid temporal slow activity), but were not position-dependent and were judged unlikely to be related to OT. Tremor artifact while standing was noted in all subjects, however it was measurable in 26 with frequency in the OT range in 25. When compared with EMG, the average difference in frequency was small at 1.2 Hz (range 0.5–2.5, p 0.46). Visual EEG analysis in OT patients did not reveal electrographic abnormalities even upon standing unassisted. Discussion: EEG was normal on this prospective, relatively large OT series. Clinicians interpreting video-EEGs should be aware of the OT artifact that can be seen in EEG and EKG leads mostly while standing.